2013
DOI: 10.1111/j.1444-0938.2012.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of corneal melting following kerato‐refractive surgery

Abstract: Corneal melting is a rare complication that may occur following a number of different types of surgery. Keratolysis may lead to scarring, irregular astigmatism, photophobia and decreased vision. This article reviews the incidence, pathophysiology and treatment of this condition in kerato-refractive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…There are limited histopathological and biochemical studies of NICM, and those reported are based on one or few cases; more data are available for corneal melt associated with autoimmune diseases and postoperative corneal melt. 36,90,92,104 The presence and role of inflammatory cell infiltration (white blood cells [WBCs]) in response to NSAID-induced corneal ulceration are controversial. Some authors observed a nonspecific inflammatory response in a case of ulcerative keratolysis induced by diclofenac and speculated that the infiltrating cells, perhaps along with the epithelial cells, released MMPs that lysed the collagen of the corneal stroma.…”
Section: The Pathogenesis Of Corneal Meltmentioning
confidence: 99%
“…There are limited histopathological and biochemical studies of NICM, and those reported are based on one or few cases; more data are available for corneal melt associated with autoimmune diseases and postoperative corneal melt. 36,90,92,104 The presence and role of inflammatory cell infiltration (white blood cells [WBCs]) in response to NSAID-induced corneal ulceration are controversial. Some authors observed a nonspecific inflammatory response in a case of ulcerative keratolysis induced by diclofenac and speculated that the infiltrating cells, perhaps along with the epithelial cells, released MMPs that lysed the collagen of the corneal stroma.…”
Section: The Pathogenesis Of Corneal Meltmentioning
confidence: 99%
“…To begin with, it has been described that epithelial ingrowth in patients undergoing laser in situ keratomileusis can lead to flap necrosis by obstructing the diffusion of nutrients through the cornea as it creates an impermeable barrier for nutrients and expresses apoptotic signals. 30,31 Cell death represents the main stimulus for corneal stromal reaction, remodeling and eventually melting. In our case, the groove was created in the sclera approximately 3 mm from the limbus, and hence, it is fairly unlikely that epithelial cells migrated through the scleral canal and settled in the stromal pocket.…”
Section: Discussionmentioning
confidence: 99%